Characteristics and outcomes of patients with or without a bleeding event: results from the triple antiplatelets for reducing dependency in ischaemic stroke (TARDIS) trial - Woodhouse, Lisa J.; Flaherty, Katie; Appleton, Jason P.; Sprigg, Nikola; Bath, Philip M.W. (2018)
Background: Several studies showed that hyperglycaemia is associated with poorer prognosis in intracerebral haemorrhage. We explored the characteristics and outcomes of patients with hyperglycaemia in the Tranexamic acid in IntraCerebral Haemorrhage-2 (TICH-2) trial. Methods: Of the 2325 patients recruited, 2028 with available baseline glucose levels were included for analysis. Baseline characteristics, radiological and clinical outcomes were compared between patients with admission glucose levels of <7.8 and ≥7.8 mmol/L (hyperglycaemia). Results: 545 (26.9%) patients had hyperglycaemia and did not differ from normoglycaemic patients in age (69.3 years vs 68.7 years) and sex (female: 246, 45.1% vs 641, 43.2%). Hyperglycaemic patients were more likely to be diabetic (187, 34.3% vs 94, 6.3%), have worse NIHSS (13.8 ± 7.7 vs 12.1 ± 7.1), larger baseline haematoma (30.2 ± 31.5 mL vs 21.2 ± 24.3 mL) and perihaematomal oedema volumes (15.8 ± 18.1 mL vs 11.7 ± 14.1 mL). There were no significant differences in haematoma expansion and increase in oedema volume between the two groups (table). Hyperglycaemia did not increase the risk of death or worse modified Rankin Scale at day 90 after adjusting for covariates including baseline haematoma volume. Discussion: Hyperglycaemia was associated with larger haematomas and more severe stroke on admission but did not result in worse outcomes after accounting for baseline haematoma volume.